Attrition during neoadjuvant chemotherapy for gastric adenocarcinoma is associated with decreased survival: A United States Safety‐Net Collaborative analysis. Issue 8 (11th August 2021) - Kronenfeld, Joshua P.; Collier, Amber L.; Turgeon, Michael K.; Ju, Michelle; Alterio, Rodrigo; Wang, Annie; Fernandez, Manuel; Porembka, Matthew R.; Richter, Harry; Lee, Ann Y.; Russell, Maria C.; Merchant, Nipun B.; et al.
Abstract: Background: Neoadjuvant chemotherapy (NAC) is standard management for localized gastric cancer (GC). Attrition during NAC due to treatment‐related toxicity or functional decline is considered a surrogate for worse biologic outcomes; however, data supporting this paradigm are lacking. We investigated factors predicting attrition and its association with overall survival (OS) in GC. Methods: Patients with nonmetastatic GC initiating NAC were identified from the US Safety‐Net Collaborative (2012–2014). Patient/treatment‐related characteristics were compared between attrition/nonattrition cohorts. Cox models determined factors associated with OS. Results: Of 116 patients initiating NAC, attrition during prescribed NAC occurred in 24%. No differences were observed in performance status, comorbidities, treatment at safety‐net hospital, or clinicopathologic factors between cohorts. Despite absence of distinguishing factors, attrition was associated with worse OS (median: 11 vs. 37 months; p = 0.01) and was an independent predictor of mortality (hazard ratio [HR]: 4.7, 95% confidence interval [CI]: 1.5–15.2; p = 0.02). Fewer patients with attrition underwent curative‐intent surgery (39% vs. 89%; p < 0.001). Even in patients undergoing surgical exploration ( n = 89), NAC attrition remained an independent predictor of worse OS (HR: 50.8, 95% CI: 3.6–717.8; p = 0.004) despite similar receipt of adjuvant chemotherapy. Conclusion: Attrition during NAC for nonmetastatic GC is independently associated with worse OS, even in patients undergoing surgery. Attrition during NAC may reflect unfavorable tumor biology not captured by conventional staging metrics.